Applied knowledge test for the MRCGP questions and answers for the AKT - A-Ali, Nuzhet (Scion Publishing, 2014)
This much expanded fourth edition features over 500 questions in all the formats used in the AKT paper. The questions are based on everyday practice scenarios, and many new questions have been added which cover those topics which the RCGP has identified as causing particular problems for candidates